The Smithsonian atlas of the Amazon - Goulding, Michael; Barthem, Ronaldo; Ferreira, Efrem Jorge Gondim (Washington [D.C.] : Smithsonian Institution Press, 2003)
Describes the rivers and regions of the Amazon river system and basin, and provides 150 color maps and nearly three hundred color photos.
Includes bibliographical references (p. 232-246) and index.
Reference and Research Book News.
Adult
Keywords: Geomorphology -- Brazil -- Amazon River Watershed; Rivers -- Brazil -- Amazon River Watershed; Stream ecology -- Brazil -- Amazon River Watershed; Physical geography -- Amazon River Watershed; Rivers -- Amazon River Watershed; Stream ecology; Amazon River Watershed; Amazon River Watershed